Black nurses in the nursing profession in Canada: a scoping review - Keisha Jefferies; Chelsa States; Vanessa MacLennan; Melissa Helwig; Jacqueline Gahagan; Wanda Thomas Bernard; Marilyn Macdonald; Gail Tomblin Murphy; Ruth Martin-Misener (BMC, 2022)
Abstract Background With migration occurring over a series of centuries, dating back to the 1600's, the circumstance regarding Black people in Canada is a complex account. A plethora of social issues and the failure to adequately acknowledge and reconcile historical issues, has resulted in health inequity, disparities and knowledge gaps, related to the Black population in Canada. In nursing, historical records indicate a legacy of discrimination that continues to impact Black nurses. The profession has begun reckoning with anti-Black racism and the residual effects. This scoping review sought to chart the existing evidence on Black nurses in the nursing profession in Canada. Methods JBI methodology was used to search peer-reviewed evidence and unpublished gray literature. Sources were considered for inclusion based on criteria outlined in an a priori protocol focusing on: 1) Canada 2) Black nurses and 3) nursing practice. No restrictions were placed on date of publication and language was limited to English and French. All screening and extractions were completed by two independent reviewers. Results The database search yielded 688 records. After removing duplicates, 600 titles and abstracts were screened for eligibility and 127 advanced to full-text screening. Eighty-two full-text articles were excluded, for a total of 44 sources meeting the inclusion criteria. Seven sources were identified through gray literature search. Subsequently, 31 sources underwent data extraction. Of the 31 sources, 18 are research (n = 18), six are commentaries (n = 6); one report (n = 1) and six are classified as announcements, memoranda or policy statements (n = 6). The review findings are categorized into five conceptual categories: racism (n = 12); historical situatedness (n = 2); leadership and career progression (n = 7); immigration (n = 4); and diversity in the workforce (n = 4). Conclusions This review reveals the interconnectedness of the five conceptual categories. Racism was a prominent issue woven throughout the majority of the sources. Additionally, this review captures how racism is exacerbated by intersectional factors such as gender, class and nationality. The findings herein offer insight regarding anti-Black racism and discrimination in nursing as well as suggestions for future research including the use of diverse methodologies in different jurisdictions across the country. Lastly, the implications extend to the nursing workforce in relation to enhancing diversity and addressing the ongoing nursing shortage.